Waging War, Planning Peace : U.S. Noncombat Operations and Major Wars - Rapport, Aaron (Book collections on Project MUSE., 2015)
As the U.S. experience in Iraq following the 2003 invasion made abundantly clear, failure to plan properly for risks associated with post-conflict stabilization and reconstruction can have a devastating impact on the overall success of a military mission. This book investigates how U.S. presidents and their senior advisers have managed vital noncombat activities while the nation is in the midst of fighting or preparing to fight major wars. It argues that research from psychology - specifically, construal level theory - can help explain how individuals reason about the costs of post-conflict noncombat operations that they perceive as lying in the distant future.